Is India Emerging as a Hub for Digital Twin Research? A Scientometric Inquiry - Dey, Kishore; Chakraborty, Dipanjali (Information Research Communications, 2026)
Introduction Digital Twin represents a revolutionary technological paradigm that has attracted considerable interest from various fields of research. Objectives This work performs scientometric analysis in order to explore the dynamics and development of digital twin research paying special attention to Indian contributions. Methodology Information was collected from OpenAlex database on May 26, 2025, based on the keywords "digital twin" in the title and abstract fields with regard to works published only in English by Indian researchers within the period of 2015-2024. In total, 1,237 records were subjected to scientometric analysis in Microsoft Excel. Results It should be noted that the research output exhibits steady growth with dominance of scientific articles in scientific communication. Indian contributions to international research in the field of digital twin have increased throughout the years under investigation. As can be seen from the authorship analysis, there is a clear tendency towards collaboration, which is evident from a high level of collaboration among researchers. In terms of author productivity, the results of analysis demonstrate skewness, similar to Lotka's law, according to which the largest number of authors publish one paper each. Key Findings Steady increase in digital twin research output from Indian researchers (2015-2024). Publication Type: Scientific articles dominate the research communication landscape - Collaboration Trend: High level of collaborative research among authors - Author Productivity Distribution: Follows Lotka's law pattern with most authors contributing single publications - Sample Size: 1,237 English-language records analyzed - Data Source: OpenAlex database -Geographic Focus: Indian research contributions to the global digital twin field.
Keywords: Author Productivity; Digital Twin; India; Lotka’s Law; OpenAlex; Scientometric.